Content Analysis of Female Associations in Print Advertising: An Example from Moroccan Magazines - Nabil, MORCHID (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Advertising is a consequential means of mass communication. Advertising practices are meticulously planned to impact on the public’s taste for distinct products or services. The influence of advertising on the public is not without danger. This study aims to assess the sex-role portrays of women in Moroccan print advertisements. Four hypothesises are made about the under-representations of women in Moroccan print advertising. The data were obtained from five Moroccan magazines issued in May, 2014. Content analysis was used under a mixed-method paradigm. Quantitative content analysis was used to yield quantifiable data for the purpose of frequency analysis of female role portrayals. Simultaneously, Qualitative content analysis was deployed to enable interpretive modes of enquiry on a limited range of advertising content. The findings from this study corroborate the stereotypical associations of women in Moroccan print advertisements and thereby document print advertising practises that are untrue to the welfare of the female society.